Антропология восприятия Дэвида Хауза - Соколовский, Сергей Валерьевич (Сибирские исторические исследования)
Рец. на кн.: David Howes. Sensorium. Contextualizing the senses and cognition in history and across cultures. Cambridge: Cambridge, 2024. 86 p. ISBN: 978-1009517225